The ABILITY OF STUDENTS AT THE TWELFTH GRADE IPA 1 AND IPA 2 OF SMAN 12 SINJAI IN TRANSLATING DESCRIPTIVE TEXT USING PAPER DICTIONARY AND ONLINE DICTIONARY (A COMPARATIVE STUDY) - Andi Mentari Nurul Putri; Hasmiati (JLE: Journal of Literate of English Education Study Program, 2021)
This research aimed to find out the differentiation between the result of the translating descriptive text using manual dictionary in the twelfth grade IPA 1 and using online dictionary in the twelfth grade IPA 2 SMAN 12 Sinjai. This research was a comparative study using a quantitative approach. The samples of this research were students of twelfth grade IPA 1 and IPA 2. The methods of data collection were tests and questionnaires. While the data analysis used descriptive analysis of the percentage score of students' ability. The results showed that there was the differentiation between the result of the translating descriptive text using manual dictionary and online dictionary. It was found that in the twelfth grade IPA 1, the percent of score was 82, 1% with the mastery level or predicate was excellent where 185 (61,7%) data was included in accurate category, 132 (44%) data was included in readable category, and 109 (36,3%) data was included in acceptability category. While in the twelfth grade IPA 2, the percent of score was 76.4% with the mastery level or predicate was good where 153 (51%) data was included in accurate category, 127 (42,3%) data was included in readable category, and 102 (34%) data was included in acceptability category.